Matched-paired analysis of patients treated for invasive mucormycosis: standard treatment versus posaconazole new formulations (MoveOn) - Salmanton-García, Jon; Seidel, Danila; Koehler, Philipp; Mellinghoff, Sibylle C; Herbrecht, Raoul; Klimko, Nikolai; Ráčil, Zdeněk; Falces-Romero, Iker; Ingram, Paul; Benítez-Peñuela, Miguel-Ángel; Rodríguez, José Yesid; Desoubeaux, Guillaume; et al. (The Journal of antimicrobial chemotherapy, 2019)
BACKGROUND: First-line antifungal treatment for invasive mucormycosis (IM) consists of liposomal amphotericin B. Salvage treatment options are limited and often based on posaconazole oral suspension. With the approval of posaconazole new formulations, patients could benefit from improved pharmacokinetics, safety and tolerability. OBJECTIVES: Our aim was to assess the effectiveness of posaconazole new formulations for IM treatment. METHODS: We performed a case-matched analysis with proven or probable IM patients from the FungiScope® Registry. First-line posaconazole new formulations (1st-POSnew) and first-line amphotericin B plus posaconazole new formulations (1st-AMB+POSnew) cases were matched with first-line amphotericin B-based (1st-AMB) treatment controls. Salvage posaconazole new formulations (SAL-POSnew) cases were matched with salvage posaconazole oral suspension (SAL-POSsusp) controls. Each case was matched with up to three controls (based on severity, haematological/oncological malignancy, surgery and/or renal dysfunction). RESULTS: Five patients receiving 1st-POSnew, 18 receiving 1st-AMB+POSnew and 22 receiving SAL-POSnew were identified. By day 42, a favourable response was reported for 80.0% (n = 4/5) of patients receiving 1st-POSnew, for 27.8% (n = 5/18) receiving 1st-AMB+POSnew and for 50.0% (n = 11/22) receiving SAL-POSnew. Day 42 all-cause mortality of patients receiving posaconazole new formulations was lower compared with controls [20.0% (n = 1/5) in 1st-POSnew versus 53.3% (n = 8/15) in 1st-AMB; 33.3% (n = 6/18) in 1st-AMB+POSnew versus 52.0% (n = 26/50) in 1st-AMB; and 0.0% (n = 0/22) in SAL-POSnew versus 4.4% (n = 2/45) in SAL-POSsusp]. CONCLUSIONS: Posaconazole new formulations were effective in terms of treatment response and associated mortality of IM. While posaconazole new formulations may be an alternative for treatment of IM, the limited sample size of our study calls for a cautious interpretation of these observations.
Keywords: Matched-Pair Analysis; Registries; novorozenec; Infant, Newborn; Infant; Humans; invazivní mykotické infekce; kojenec; lidé středního věku; antifungální látky; dítě; registrace; mukormykóza; Amphotericin B; Child; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Triazoles; amfotericin B; předškolní dítě; Adult; ženské pohlaví; Male; Antifungal Agents; Middle Aged; Adolescent; Invasive Fungal Infections; Mucormycosis; Drug Compounding; příprava léků; Young Adult; analýza párové shody; triazoly; mužské pohlaví; prospektivní studie; Mucorales; Child, Preschool; mladiství; Prospective Studies